A Cross-Platform Payroll Information System for SMEs: An Agile-Scrum Approach at CV. Gema Syifa Engineering - Huda, Muhamad Fatchul; Pramudito, Dendy K; Pradini, Purnama Sakhrial (Jurnal Informatika Ekonomi Bisnis, 2025)
This study focuses on constructing an integrated payroll application utilizing web and Android platforms at CV Gema Syifa Engineering through the implementation of Agile Scrum methodology. The primary challenge motivating this research involves the company's reliance on a semi-automated compensation mechanism that necessitates manual information entry via spreadsheet documents and data storage in fragmented directories. This situation generates various operational obstacles including time wastage during payroll data insertion, elevated frequency of data validity errors, restricted information access, and complexity in remuneration computation procedures. Furthermore, the absence of system integration results in sluggish wage calculation execution, inconsistent computational outcomes, and questionable data credibility. The research approach adopts the Agile Scrum framework which facilitates adaptive and cyclical software development processes through sprint iterations. System architecture is designed by applying Unified Modeling Language (UML) notation encompassing use case representations, activity flow diagrams, interaction sequence diagrams, and database structures normalized to the third stage (3NF).Implementation outputs demonstrate that the constructed solution successfully accommodates comprehensive integration of the entire payroll workflow, spanning from personnel information administration, attendance documentation, overtime computation, to automated generation of compensation calculations and salary slip documents. The application provides layered access segregation: administrators possess full privileges for system configuration, while employees can access their personal remuneration information and attendance records. Security protection mechanisms are implemented through two-factor authentication (2FA) for administrators and automatic account locking systems following three unsuccessful login attempts. System verification through Blackbox testing approach confirms that all functionalities operate according to design parameters. This implementation proves to optimize efficiency and precision in payroll data management, minimize computational errors, and provide superior accessibility for HR divisions and workforce. The system is projected to support enhanced operational performance and human resource satisfaction at CV Gema Syifa Engineering.